The Impact of Online Mentoring in Implementing RADEC Learning to the Elementary School Teachers’ Competence in Training Students’ Critical Thinking Skills: A Case Study During COVID-19 Pandemic - Lestari, H.; Sopandi, W.; Sa'ud, U. S.; Musthafa, B.; Budimansyah, D.; Sukardi, R. R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to describe the impact of online mentoring activities in implementing the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on the competence of elementary school teachers in training students’ critical thinking skills. The method was a pre-experiment with a one-group pretest-posttest design involving 25 elementary school teachers in Indonesia. The teachers received online mentoring in implementing RADEC learning model. The research instrument was a questionnaire to measure teachers’ knowledge and skills in training critical thinking. The data processing technique was carried out by calculating the mean and the percentage of each item to obtain a description of the teachers’ knowledge and skills in training students’ critical thinking before and after treatment. The data were analyzed inferentially with a paired sample t-test using SPSS version 22 software to see the impact of the treatment on teachers’ competence in training critical thinking. Based on the results of the paired-sample t-test, for both the knowledge and skills aspects, the probability value (sig) was 0.00 <0.05. This result means that there was a significant difference in the knowledge and skills of teachers in training students’ critical thinking skills before and after mentoring activities. The study results indicate that the online mentoring in implementing the RADEC learning model improved teachers’ competence in training elementary school students’ critical thinking skills.